Peri-tumor associated fibroblasts promote intrahepatic metastasis of hepatocellular carcinoma by recruiting cancer stem cells - Jiang, Jinghua; Ye, Fei; Yang, Xue; Zong, Chen; Gao, Lu; Yang, Yang; Zhao, Qiudong; Han, Zhipeng; Wei, Lixin (Cancer letters, 2017)
Fibroblasts have been reported to play an important role in hepatocellular carcinoma (HCC). However, the role of fibroblasts have not been fully understood. Conditioned medium collected from human peri-tumor tissue-derived fibroblasts (CM-pTAFs) showed high metastasis ability than human HCC tissues-derived fibroblasts (CM-TAFs). To determine what component was secreted from fibroblasts, we used Bio-Plex analysis system and compared the factors secreted from CM-pTAFs and CM-TAFs, found a series of up-regulated cytokines in the CM-pTAFs, including IL-6, CCL2, CXCL1, CXCL8, SCGF-β, HGF and VEGF. Pretreatment of IL-6 inhibitor Tocilizumab could inhibit metastasis the HCC cell treated with CM-pTAFs in vitro and in vivo. The expression of CCR2 and CXCR1 were up-regulated after CM-pTAFs treatment in HCC cell line SMMC-7721. Flow cytometric analysis experiment showed that most CCR2 or CXCR1 positive cells were also EpCAM positive. In vitro studies also showed that CM-pTAFs could increase stemness of SMMC-7721. In addition, neutralization of SCGF-β and HGF could significantly reduce metastasis and viability of cancer stem cells treated with CM-pTAFs. Taken together, these results indicated that the peri-tumor tissues derived fibroblasts may promote development of HCC by recruiting cancer stem cells and maintaining their stemness characteristic. •Peri-tumor associated fibroblasts could promote intrahepatic metastasis of hepatocellular carcinoma.•Seven factors secreted from peri-tumor associated fibroblasts could lead to intrahepatic metastasis of cancer cells.•The cancer cells that involved with intrahepatic metastasis were include a part of cancer stem cells.